2017
DOI: 10.1007/s11998-017-9921-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing through microencapsulated agents for protective coatings

Abstract: The use of microcapsules containing healing agents, which can serve as source of self-healing for coatings, was investigated. The appropriate self-repairing coatings are designed to be used for heavy-duty corrosion protection or for the protection of moisture-sensitive substrates like wood. Microcapsules based on thermoset resins (urea–formaldehyde and melamine–formaldehyde) which contained components of different chemical natures (resins or inhibitors) were fabricated using emulsion techniques. The subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A capsule is a good type of microstorage. 39 The repairable superhydrophobic material can be obtained by dispersing microcapsules loaded with low surface energy components into the matrix material. When this material is damaged or stimulated by a certain signal, it can induce the rupture of the capsule and release the capsule core, which can repair the damaged part like the plant repairing its own damage, so that the function of the material is more lasting and has a longer service life.…”
Section: Microencapsulation Approachmentioning
confidence: 99%
“…A capsule is a good type of microstorage. 39 The repairable superhydrophobic material can be obtained by dispersing microcapsules loaded with low surface energy components into the matrix material. When this material is damaged or stimulated by a certain signal, it can induce the rupture of the capsule and release the capsule core, which can repair the damaged part like the plant repairing its own damage, so that the function of the material is more lasting and has a longer service life.…”
Section: Microencapsulation Approachmentioning
confidence: 99%
“…The results showed that the particle size of the microcapsules affect its dispersion in the coating, and then affect the curing performance of the core repair agent. Schreiner et al [ 19 ] designed a self-healing coating for metal corrosion protection or moisture sensitive substrate protection such as wood. The results showed that the self-healing coating with microcapsules had obvious advantages over the traditional protective coating.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the microcapsules containing IPDI not only enabled the coating to have self-healing properties, but also improved the thermal stability of the coating. Schreiner et al [ 27 ] prepared microcapsules with good self-healing ability by using thermosetting resins (urea-formaldehyde resin and melamine-formaldehyde) as substrates. Additionally, the self-healing process of the microcapsules needs to be carried out at a higher temperature.…”
Section: Introductionmentioning
confidence: 99%